Effects of projected climate change on winter wheat yield in Henan, China. (15th December 2022) - Zhang, Lin; Wang, Feng; Song, Hongquan; Zhang, Tianning; Wang, Dong; Xia, Haoming; Zhai, Shiyan; Liu, Yinzhan; Wang, Tuanhui; Wang, Yaobin; Min, Ruiqi
Abstract: Climate change has already affected and will continue to affect crop yields. It is essential to understand and predict how the changing climate is influencing crops. This study assessed the effects of climate change on winter wheat yields in a central province (Henan) of China by using the calibrated Agricultural Production Systems sIMulator (APSIM) and the daily climate projections for Global Climate Models (GCMs), under two future societal development pathways (SSPs), SSP126 (sustainable development with low level greenhouse gas emissions) and SSP585 (conventional development with high level greenhouse gas emissions). We found that the effects of climate change on winter wheat yield would have clear spatial and temporal variations. Climate change is expected to shorten the maturity period for winter wheat by 1.1 days dec −1 (days per decade) and 4.4 days dec −1 compared with the baseline scenario (2000–2014) under scenarios of SSP126 and SSP585, respectively. However, the flowering dates would be delayed, by 0.2 days dec −1 under the SSP126 scenario and by 0.6 days dec −1 under the SSP585 scenario. Yield showed no significant trend under both scenarios, except that it would be higher than baseline in most years. Compared with the baseline, the annual mean winter wheat yield under future climate change would increase 784 kg ha −1 (SSP126) and 332 kg ha −1 (SSP585) during the 2030s, 1172 kg ha −1 (SSP126) and 364 kg ha −1 (SSP585) during the 2060s, and 707 kg ha −1 (SSP126) and 533 kg ha −1 (SSP585) during the 2090s. In the SSP126 scenario, winter wheat yield would increase over most counties of Henan, especially during the 2060s. However, winter wheat yield would decline in northern Henan during the 2030s and 2090s under the SSP585 scenario. Our findings could help farmers develop adaptation measures for winter wheat to ensure food security in Henan and China. Highlights: The APSIM-wheat model was comprehensive calibrated in Henan, China. Simulated spatiotemporal patterns in effects of climate on winter wheat phenology and yield. Effects of climate change on winter wheat phenology of Henan were quantified. Effects of climate change on winter wheat yield of Henan were quantified.